2018
DOI: 10.1038/s41598-018-24306-1
|View full text |Cite
|
Sign up to set email alerts
|

Mutation status and prognostic values of KRAS, NRAS, BRAF and PIK3CA in 353 Chinese colorectal cancer patients

Abstract: Mutations in KRAS exon 2, BRAF and PIK3CA are commonly present in colorectal cancer (CRC) worldwide, but few data about RAS mutations outside KRAS exon 2 are available for Chinese CRCs. We, therefore, determined the mutation frequencies and prognostic values of KRAS exon 2, 3 and 4, NRAS exon 2 and 3, PIK3CA exon 9 and 20, and BRAF exon 15 by PCR and direct sequencing in 353 CRC patients from two Chinese clinical centers. KRAS exon 2, BRAF, PIK3CA mutations were identified in 42.2%, 4.5%, 12.3% of the cases, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
61
4
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(91 citation statements)
references
References 36 publications
(51 reference statements)
21
61
4
5
Order By: Relevance
“…Compared with the previous studies (Table 5 ), the mutation rate of KRAS in CRC reported in our study was consistent with that reported by Douillard et al ( 6 ) and Gao et al ( 25 ), who also focused on exons 2, codon 12/13. Guo et al ( 13 ) believed that the mutation rate of KRAS was as high as 52.7%. This conclusion may be because they included more genetic loci into the study (exons 2/3/4, codons 12/13/59/61/117/146/147).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the previous studies (Table 5 ), the mutation rate of KRAS in CRC reported in our study was consistent with that reported by Douillard et al ( 6 ) and Gao et al ( 25 ), who also focused on exons 2, codon 12/13. Guo et al ( 13 ) believed that the mutation rate of KRAS was as high as 52.7%. This conclusion may be because they included more genetic loci into the study (exons 2/3/4, codons 12/13/59/61/117/146/147).…”
Section: Discussionmentioning
confidence: 99%
“…It showed that mutations in KRAS/NRAS, BRAF and PIK3CA genes were not associated with pathological status of colorectal cancer. There are different domestic and foreign studies on the relationship between KRAS/NRAS, BRAF and PIK3CA gene mutation status and pathological characteristics in colorectal cancer, which may be related to the detection method, sample size and regional differences [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…It showed that mutations in KRAS/NRAS, BRAF and PIK3CA genes were not associated with pathological status of colorectal cancer. There are different domestic and foreign studies on the relationship between KRAS/NRAS, BRAF and PIK3CA gene mutation status and pathological characteristics in colorectal cancer, which may be related to the detection method, sample size and regional differences [41][42][43].…”
Section: Discussionmentioning
confidence: 99%